2014
DOI: 10.3201/eid2011.140468
|View full text |Cite
|
Sign up to set email alerts
|

Beijing Lineage of MDRMycobacterium tuberculosisin Bulgaria, 2007–2011

Abstract: To assess the spread of the Mycobacterium tuberculosis Beijing genotype among patients with multidrug-resistant and extensively resistant tuberculosis in Bulgaria, we genotyped 188 (72%) of 261 microbiologically confirmed resistant isolates obtained during 2007–2011. The estimated prevalence of the Beijing genotype among these patients was 3.2%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This may be expected given the overwhelming dominance of the Beijing family strain in most regions in China [ 19 , 20 ]. Consistent with previous reports [ 21 23 ], the results of genotyping indicate that Beijing family of strains is also overrepresented in this population. While different from the previous study [ 22 ], the member within Beijing family exhibit the close-relatedness with similarity more than 80 % and the 11 clones were identified with the majority clone comprised by 90 Mtb isolates, which all belong to Beijing genotype.…”
Section: Discussionsupporting
confidence: 92%
“…This may be expected given the overwhelming dominance of the Beijing family strain in most regions in China [ 19 , 20 ]. Consistent with previous reports [ 21 23 ], the results of genotyping indicate that Beijing family of strains is also overrepresented in this population. While different from the previous study [ 22 ], the member within Beijing family exhibit the close-relatedness with similarity more than 80 % and the 11 clones were identified with the majority clone comprised by 90 Mtb isolates, which all belong to Beijing genotype.…”
Section: Discussionsupporting
confidence: 92%
“…Although the Beijing lineage keeps the second position of distribution in EU/EEA (about 30% of the sequenced strains) in Bulgaria, it represents only 3% amongst the MDR-TB cases. [3] The trend of scarce spreading remains steady with the years (3.2% for the period of 2007-2011) [12] and could be explained with the small numbers of imported TB cases in the country.…”
Section: Discussionmentioning
confidence: 99%
“…In the Beijing sublineage, 70% were MDR with a probability odds ratio of 2.6. Our previous study demonstrated that the first imported TB case in Bulgaria was from Moldova in 2007-2009 [65]. Not all detected cases of TB caused by the Beijing genotype resulted from human migration.…”
Section: Resultsmentioning
confidence: 99%